The Role of E-AYVP (ASEAN Youth Volunteer Program) 2021 as a Public Diplomacy In Fostering ASEAN Youth to Achieve The Goals of ASCC 2025 [Peran E-AYVP (ASEAN Youth Volunteer Program) 2021 sebagai Diplomasi Publik Dalam Membina Pemuda ASEAN Untuk Mencapai] - Al-Ayubi, M. Solahudin; Rijal, Najamuddin Khairur (Jurnal Politica, 2023)
The ASEAN Youth Volunteer Program (AYVP) is an annual volunteer program held under the auspices of the Ministry of Youth and Sports Malaysia with the support of the U.S. Agency for International Development (USAID). The permanent secretariat of this program is based in Universiti Kebangsaan Malaysia (The National University of Malaysia - UKM). This program has been running and giving an impact on increasing ASEAN youth capabilities and knowledge, providing an understanding of issues in ASEAN, supporting cultural exchange and learning, and strengthening ASEAN regional identity for youth. In 2021, AYVP conducted an e-AYVP addressing the theme “Strengthening ASEAN Education Delivery Systems in Challenging Times”. Through a descriptive-qualitative approach, this research will explain the role of e-AYVP 2021 as public diplomacy in fostering ASEAN youths to pursue the goals of ASEAN Socio-Cultural Community (ASCC) 2025. This research uses the concept of public diplomacy and soft power by Joseph Nye. As the finding, e-AYVP 2021 as the non-state actor of soft power has fostered the ASEAN youth to accelerate the actualization of ASCC 2025 A.1, A.2, B.1, B.2, B.3. The result is based on the assessment of the e-AYVP 2021 program through the concept of public diplomacy and soft power through the analytical process of the concept, the ASCC 2025 blueprint, online survey and interviews.AbstrakASEAN Youth Volunteer Program (AYVP) adalah program sukarelawan tahunan yang diselenggarakan di bawah naungan Kementerian Pemuda dan Olahraga Malaysia dengan dukungan dari U.S. Agency for International Development (USAID). Sekretariat tetap program ini berkedudukan di Universiti Kebangsaan Malaysia (Universitas Nasional Malaysia - UKM). Program ini telah berjalan dan memberikan dampak terhadap peningkatkan kapabilitas dan pengetahuan pemuda ASEAN, memberikan pemahaman tentang isu-isu di ASEAN, mendukung pertukaran budaya dan pembelajaran, serta memperkuat identitas kawasan ASEAN untuk para pemuda. Pada tahun 2021, AYVP melaksanakan e-AYVP dengan mengangkat tema “Memperkuat Sistem Penyelenggaraan Pendidikan ASEAN di Masa Menantang”. Melalui pendekatan deskriptif-kualitatif, penelitian ini akan menjelaskan bagaimana peran e-AYVP 2021 sebagai diplomasi publik untuk pemuda ASEAN. Penelitian ini menggunakan konsep diplomasi publik dan soft power dari Joseph Nye. Sebagai temuan, e-AYVP 2021 sebagai aktor non-negara dari soft power telah membina pemuda ASEAN untuk mempercepat aktualisasi ASCC 2025 A.1, A.2, B.1, B.2, B.3. Hasil tersebut berdasarkan pengujian program e-AYVP 2021 melalui proses analitis dari konsep, cetak biru ASCC 2025, survei online dan wawancara.